Association of Cardiovascular Disease with Micro Albuminuria in Type 2 Diabetes Mellitus - Study in A Tertiary Care Hospital (Journal of Medicine, 2020)
Introduction: Microalbuminuria appears to be the earliest sign and predictor of the subsequent diabetic renal disease and is a marker of increased cardiovascular morbidity and mortality. It is also a predictor of morbidity and mortality in patients who do not have evidence of significant renal diseaseObjective: To evaluate the association of microalbuminuria in type 2 DM with cardiovascular diseases and to correlate microalbuminuria with age of onset in type 2 diabetes mellitus.Materials and Method: A hospital based observational study was carried out in the Department of Medicine, Dhaka Medical College & Hospital,Dhaka, from January 2014 to November 2014. A total of 100 patients diagnosed as type 2 diabetes mellitus according to American Diabetic Association guideline were included in this study. Association of microalbuminuria with cardiovascular diseases was determined by statistical analysis and regression analysis.Results: The majority (40.0%) of patients were in 5th decade and the mean (±SD) age was 57.17±11.2 years. According to BMI it is observed that majority of patients were obese in both groups, where male 66.0% and female 75.5%.The occurrence of cardiovascular diseases in type 2 diabetes mellitus patients is increasing with duration of DM, where 61.9% found in newly diagnosed DM. It was observed that 38(38.0%) patients had normoalbuminuria (